Kontestasi Hadis dalam Tagar Potong Kuku (#PotongKuku) Di Media TikTok - Fachruli Isra Rukmana, Syahidil Mubarik MH, Sri Kurniati Yuzar (Al-Qudwah)
The study of hadiths through hashtags on social media is a new phenomenon in the disruption era. Before the widespread use of technology, people learned the hadiths of the Prophet through gatherings held directly in mosques and religious schools. However, technological advancements have made it possible to study the hadiths of the Prophet through online media, proving that the hadiths of the Prophet have undergone very dynamic progress. One trending study of the Prophet's hadiths is the use of the hashtag #potongkuku. One of the posts under this hashtag includes a clip of a sermon delivered by Habib Rifky Alaydrus. This paper aims to investigate the urgency of falsification in understanding the Prophet's hadiths on the #potongkuku hashtag on the TikTok application, as well as recommendations, responses, and the urgency of falsification for Muslims in the online world. This type of research is qualitative. Primary data sources are taken from posts under the #potongkuku hashtag on the TikTok application, while secondary data are taken from literature related to the discussed theme. The results of this study indicate that hashtags on TikTok can facilitate users in finding relevant content they need, such as the theme of cutting nails in hadiths. The large amount of da'wa content discussing cutting nails has received responses from TikTok users, both positive and negative. The urgency of falsification in understanding the Prophet's hadiths is very necessary, considering that there are scholars who convey hadiths without valid sources regarding the recommendation of cutting nails in the Prophet's hadiths. The #potongkuku hashtag has emerged as a means to study the Prophet's hadiths and plays a significant role in accessing hadith studies through smartphones. Furthermore, the #potongkuku hashtag has also contributed positively to the image of Islam in the eyes of the world through social media.